(untitled) (The Pakistan Development Review, 2008)
Rapid rises in the prices of crude oil in the decade of 2000s have raised concerns among policy-makers around the world, as the theoretical and empirical literature has established that oil price shocks may have an adverse impact on the macro economy of the country. In particular, for the oil importing developing countries like Pakistan, this upward trend in the price of oil can have serious repercussions in terms of creating inflationary pressures in the economy, increasing budget deficit and balance of payment problems, and thus affecting the GDP growth. Pakistan was on the path of rising GDP growth in the first seven years of this decade. But in the year 2007-08, the situation has changed. This oil price shock could possibly be one of the reasons. As an impact of rising growth rate of GDP, demand for energy has also gone up rapidly in this period. In the energy mix for the year 2005-06, oil accounts for 32 percent of the total energy used in Pakistan, and it is the second largest source of energy used after natural gas, which accounts for 39 percent. With oil being the second largest source of energy used along with almost constant rate of its production Pakistan is heavily dependent on oil imports from Middle East exporters (Saudi Arab playing the lead role). Almost 82 percent of the demand for petroleum products in the country is met through imports.1 Pakistan spent about 44 percent of export earnings on oil imports in 2006-07. This percentage was only 27 percent in 2004-05. Therefore, the international oil price increase has a direct impact on the macro economy of the country, especially on the oil price GDP relationship. The share of net oil imports in GDP is an indicator of the relative importance of the oil price rise to the economy in terms of the potential adjustments needed to offset it. For Pakistan over the last few years, this ratio has risen from 3.13 in 1990-91 to -5.24 in 2005-06 [Malik (2007)]. With such a high ratio, unless country is running in surplus, or has extremely large foreign exchange reserves, high oil price is dealt by severe macro economic adjustments.